Hakikat Manusia (Peserta Didik) Sebagai Makhluk Pedagogik - Kartini, Kartini; Muljono, Muljono; Yuspiani, Yuspiani (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to find out the nature of human beings (students) as pedagogic beings. This article uses the literature study method to explore the concept of human beings (students) as pedagogical beings. The literature review process begins with the identification of relevant sources, including journal articles, books, conference papers, and peer-reviewed scientific articles that discuss the essence of humanity and its relationship with education. Data analysis techniques using critical analysis are used to evaluate various theoretical frameworks that discuss the relationship between humanity and education. The results of the analysis show that humans as pedagogic creatures are humans who have the potential to be educated and educated, and the nature of humans (learners) as pedagogic creatures, based on nature that has the basic potential of hearing, vision, and heart as instruments in the educational process. Humans are creatures that can be educated and educated (homo educandum). The educational process that makes human beings the subject and object of education. Students as pedagogical creatures will describe that they have various characteristics and potentials that need to be understood in the context of education. This understanding is essential to creating a learning environment that supports their psychic and spiritual development optimally